The Effect of Principal's Leadership on the Performance of Elementary School Teachers in Tiworo Islands District - La Ubi Ubi (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2021)
This study aimed to analyze the influence of the principal's leadership on the performance of elementary school teachers in the Tiworo Islands sub-district. The sample in this study was 67 respondents. This study uses a quantitative approach. Principal leadership and teacher performance data were obtained using a questionnaire. The results of the inferential analysis concluded that the value of sig. = 0.000 < = 0.05, meaning that the principal's leadership has a positive effect on the performance of elementary school teachers in the Tiworo Islands sub-district